Anesteziološke posebnosti laparoskopske bariatrične kirurgije - Uranjek, Jasna (Endoskopska revija, 2007)
Background. Obesity and its associated comorbidities put the patient undergoing bariatric surgery at increased risk for anaesthesia-related complications.Methods. Forty-two anaesthesia charts of morbidly obese patientssubjected to laparoscopic bariatric surgery were analysed retrospectively with a special attention being given to respiratory function tests. Results. Preoperative anaesthesiologic examination revealed one to several coexisting conditions in 69 % of all patients. Average vital capacity (VC) before the operation was 98. 36 % of the predicted value; arterial blood gas analyses were normal. Severe long-term anaesthesia-related complications or prolonged awakening from anaesthesia were not recorded. The postoperative VC was on average 29.50 % lower than the preoperative value. There was a statistically significant increase (p<0. 05) in postoperative pCO2 levels, however without clinical manifestations. Conclusions. From the anaesthesiological point of view, a bariatric patient needs appropriate preoperative evaluation, intense intraoperative monitoring, optimal anaesthesiological medication and proper postoperative care with optimal analgesia.
Keywords: laparoskopija; bariatrična kirurgija; anestezija